2006
DOI: 10.1107/s0021889806017122
|View full text |Cite
|
Sign up to set email alerts
|

Analytical formulation of the variance method of line-broadening analysis for Voigtian X-ray diffraction peaks

Abstract: An alternative formulation of the variance method for the line-broadening analysis of polycrystalline materials is presented. It maintains the theoretical basis of the earlier formulations of the variance method, but differs in the manner of calculating the variance coefficients of the line profiles. In the proposed formulation, these are evaluated analytically in terms of the shape parameters of Voigt functions fitted to the X-ray diffraction data. Explicit expressions are thus derived for calculating the (su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…With increasing ball milling time, it is observed that the integral breadth of the Lorentz component (β L ) increases from 0.0004 • for the as-purchased LiH to 0.2132 • for the 180 min ball-milled LiH, whereas, on the contrary, the integral breadth of the Gauss component (β G ) remains the same at the as-purchased condition of 0.46 • . Clearly, the unchanged β G is incompatible with the introduction of lattice defects within the LiH crystals during ball milling, since the attendant internal stresses would induce additional Gauss broadening [41]. On the other hand, the increased β L is entirely consistent with the crystallite size refinement from the micrometer range to the nanometer range, since the presence of LiH nano-crystals would induce additional Lorentz broadening [41].…”
Section: Xrd Analysis Of the Ball Milling Time Effectmentioning
confidence: 77%
See 2 more Smart Citations
“…With increasing ball milling time, it is observed that the integral breadth of the Lorentz component (β L ) increases from 0.0004 • for the as-purchased LiH to 0.2132 • for the 180 min ball-milled LiH, whereas, on the contrary, the integral breadth of the Gauss component (β G ) remains the same at the as-purchased condition of 0.46 • . Clearly, the unchanged β G is incompatible with the introduction of lattice defects within the LiH crystals during ball milling, since the attendant internal stresses would induce additional Gauss broadening [41]. On the other hand, the increased β L is entirely consistent with the crystallite size refinement from the micrometer range to the nanometer range, since the presence of LiH nano-crystals would induce additional Lorentz broadening [41].…”
Section: Xrd Analysis Of the Ball Milling Time Effectmentioning
confidence: 77%
“…Clearly, the unchanged β G is incompatible with the introduction of lattice defects within the LiH crystals during ball milling, since the attendant internal stresses would induce additional Gauss broadening [41]. On the other hand, the increased β L is entirely consistent with the crystallite size refinement from the micrometer range to the nanometer range, since the presence of LiH nano-crystals would induce additional Lorentz broadening [41].…”
Section: Xrd Analysis Of the Ball Milling Time Effectmentioning
confidence: 77%
See 1 more Smart Citation
“…36,37 Second, the nitrogen solutes have introduced structural defects into the lattice of the YAG crystals because their peaks in PLPS SiC-N 2 exhibit additional Gaussian broadening with respect to PLPS SiC-Ar, and the XRD theory establishes that lattice defects introduce Gaussian broadening whereas the nanocrystallites induce Lorentzian broadening. 38 Fig. 3 are the specific mass-change curves for PLPS SiC-Ar and PLPS SiC-N 2 isothermally oxidized in air at 1100-1450 • C. As can be seen, there exist appreciable differences between the oxidation kinetics of the two materials.…”
Section: Microstructure Of the As-processed Samplesmentioning
confidence: 92%
“…The crystallite size and the lattice microstrains of 3D copper were evaluated by analytical formulation of the variance method of line-broadening analysis of Voigt functions using as fitting curves of X-ray diffraction peaks [9]. The X-ray diffraction (XRD) (X-Pert, Phillips) had a Bragg-Brentano configuration and Co(K␣) anticathode.…”
Section: Methodsmentioning
confidence: 99%